Editorial: de novo inflammatory bowel disease following bariatric surgery—potential implications for research and clinical practice. Issue 11 (June 2018) - Alukaidey, S.; Heerasing, N.
Abstract : Linked Content This article is linked to Ungaro et al and Ungaro and Colombel papers. To view these articles visithttps://doi.org/10.1111/apt.14569 andhttps://doi.org/10.1111/apt.14667 .